RACKING DESCENT FROM THE WHEEL FLANGE ON THE RAIL - Taturevych, O. O. (Science and Transport Progress, 2003)
The results of the basic researches a stated on the improvement of the methods of determination of the stability factor of derailing. The studies were conducted on the grounds of analysis of concrete events of the accidents and derailing. The average values of the probability of simultaneous combination of disadvantageous factor obtained as a result of the investigations.